Practical Vessel Imaging by Computed Tomography in Live Transgenic Mouse Models for Human Tumors - Gordon L. Kindlmann; David M. Weinstein; Greg M. Jones; Christopher R. Johnson; Mario R. Capecchi; Charles Keller (Molecular Imaging)
Contrast-enhanced small-animal computed tomography is an economical and highly quantitative tool for serially examining tumor development in situ, for analyzing the network of blood vessels that nourish them, and for following the response of tumors to preclinical therapeutic intervention(s). We present practical considerations for visualizing the vascular network of transgenic mouse tumors. Using a long-acting iodinated triglyceride blood-pool contrast agent, we present optimized scanner acquisition parameters and volume-rendering techniques for examining the intermediate and large vessels of complex spontaneous tumors (e.g., alveolar rhabdomyosarcomas) in transgenic mice. Our findings indicate that multiple-frame, 360–720 view acquisitions were mandatory for clarifying bone and soft tissue from vessel contrast. This finding was consistent in visualizations using a one-dimensional transfer function where voxel color and opacity was assigned in proportion to CT value and a two-dimensional transfer function where voxel color and opacity was assigned in proportion to CT value and gradient magnitude. This study lays a groundwork for the qualitative and quantitative assessment of anti-angiogenesis preclinical studies using transgenic mice.